Separable Equations
Here is where we start looking at differential equations that are more complex than y' = f(x). We will look at some techniques that can be used. Please note that no one technique will analytically solve all differential equations.
When solving differential equations, sometimes intuition, good algebra, and perhaps luck, we can separate variables of a firstorder ordinary differential equation into the form of:
f(x) dx + g(y) dy = 0
[y is a function of x]
Taking the integral of each variable separably will yield:
∫ f(x) dx + ∫ g(y) dy = ∫ 0 dx
∫ f(x) dx + ∫ g(y) dy = C
We could also see the form:
f(x) dx = g(y) dy
∫ f(x) dx = ∫ g(y) dy
The answer could take either form:
∫ f(x) dx + C = ∫ g(y) dy, or
∫ f(x) dx = ∫ g(y) dy + C
Remember C is just an arbitrary constant. If we have initial conditions attached to the differential equation, then we can solve for C.
At this point, we may or may not be able to explicitly solve for y. The best way to tell whether a differential equation is separable is by practice and experience. Let's look at a few examples.
1. y^2 * y' = x^2
y' is short notation for dy/dx (or dy/dt if the dependent variable is t).
y^2 * y' = x^2
y^2 * dy/dx = x^2
y^2 dy = x^2 dx
∫ y^2 dy = ∫ x^2 dx + C
y^3/3 = x^3/3 + C
Solving for y, we get y = (x^3 + C/3)^(1/3).
2. e^(yx)*dy/dx = 1
e^(yx)*dy/dx = 1
e^y * e^(x) * dy/dx = 1
e^y * dy = e^x * dx
∫ e^y dy = ∫ e^x dx + C
e^y = e^x + C
Solving for y, we get y = ln (e^x + C).
3. dy/dx = y^2  6*y + 9
dy/dx = y^2  6*y + 9
Diving by y^2  6*y + 9, (making an assumption that y ≠ 3 which we are not dividing by zero),
dy/dx * 1/(y^2  6*y + 9) = 1
dy/(y^2  6*y + 9) = dx
dy/(y  3)^2 = dx
∫ dy/(y  3)^2 = ∫ dx
1/(y  3) = x + C
1/(3  y) = x + C
3  y = 1/(x + C)
y = 3 + 1/(x + C)
y = 3  1/(x + C)
Here is a separable differential equation with an initial condition:
4. y' = y^2 * x^3, y(1)=4
Solve the differential equation first:
dy/dx = y^2 * x^3
y^2 dy = x^3 dx
∫ y^2 dy = ∫ x^3 dx
1/y = x^4/4 + C
y = 1/(x^4/4 + C)
y = 1/(x^4/4 + C)
Now using the initial condition y(1)=4,
4 = 1/(1/4 + C)
4 * (1/4 + C) = 1
1 + 4*C = 1
C = 1/2
The final answer is y = 1/(x^4/4 + 1/2).
The next time we talk on this subject we will be looking at integrating factors. Eddie
This blog is property of Edward Shore. 2013
A blog is that is all about mathematics and calculators, two of my passions in life.
Thursday, August 15, 2013
Differential Equations #2: Separable Differential Equations
Subscribe to:
Post Comments (Atom)
Expanding Linear Regression
Expanding Linear Regression Introduction – Linear Regression All scientific calculators that have twovariable dimensions has cu...

Casio fx991EX Classwiz Review Casio FX991EX The next incarnation of the fx991 line of Casio calculators is the fx991 EX. ...

TI36X Pro Review This is a review of the TI36X Pro Calculator by Texas Instruments. History Originally, this was the TI30X Pro that w...

One of the missing features of the TI82/83/84 family is the ability to convert between bases. Here are two programs in TIBasic to help...
No comments:
Post a Comment